2021
DOI: 10.3390/coatings11060688
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Influences of Hot Streak and Swirl on the Cooling Performances of C3X Guide Vane with or without TBCs

Abstract: This paper studied the combined influences of the hot streak and swirl on the cooling performances of the NASA C3X guide vane coated with or without thermal barrier coatings (TBCs). The results show that: (1) Even under uniform velocity inlet conditions, the hot streak core can be stretched as it impinges the leading edge which causes higher heat load on the suction side of the forward portion. (2) The swirl significantly affects circumferential and radial migration of the hot streak core in the NGV passage. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This is primarily attributed to the flow acceleration originating from the stagnation line on the SS. Shi et al [22] conducted experiments on the inlet plane of the passage; the presence of positive swirls resulted in an elevated temperature in the tip region on the SS. Conversely, when a negative swirl was introduced, it led to a higher temperature in the hub region on the PS.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily attributed to the flow acceleration originating from the stagnation line on the SS. Shi et al [22] conducted experiments on the inlet plane of the passage; the presence of positive swirls resulted in an elevated temperature in the tip region on the SS. Conversely, when a negative swirl was introduced, it led to a higher temperature in the hub region on the PS.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the HS significantly increased the non-uniformity of the heat load distribution over the blade surface. Shi [12] studied the effect of the HS on the overall cooling performance of the turbine vane additional TBCs and film cooling. They concluded that TBCs could reduce the influence of the hot streaks on the overall cooling performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies that have been performed, more attention has been placed on the uncoated vane. Information on the influence on the coated stator vane and the coated rotor blade is still less common in the open literature, especially for the coated rotor blade [18][19][20][21]. For the coated rotor blade, a wide variety of factors are known to contribute to the complexity of aerothermal and TBC insulation performance, which include the hot streak, the residual swirl, high levels of mainstream turbulence and unsteadiness, rotational effects, and rotor-stator interaction [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%